After war times : an African American childhood in reconstruction-era Florida - Fortune, Timothy Thomas, 1856-1928 (The University of Alabama Press, 2014)
T. Thomas Fortune was a leading African American publisher, editor, and journalist of the late nineteenth and early twentieth centuries, who was born a slave in antebellum Florida lived through emancipation, and rose to become a literary lion of his generation. In T. Thomas Fortune''s "After War Times," Daniel R. Weinfeld brings together a series of twenty-three autobiographical articles Fortune wrote about his formative childhood during Reconstruction and subsequent move to Washington, DC. By 1890 Fortune had founded a predecessor organization to the National Association for the Advancement o